4(x-2)-7x=1

Simple and best practice solution for 4(x-2)-7x=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-2)-7x=1 equation:


Simplifying
4(x + -2) + -7x = 1

Reorder the terms:
4(-2 + x) + -7x = 1
(-2 * 4 + x * 4) + -7x = 1
(-8 + 4x) + -7x = 1

Combine like terms: 4x + -7x = -3x
-8 + -3x = 1

Solving
-8 + -3x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -3x = 1 + 8

Combine like terms: -8 + 8 = 0
0 + -3x = 1 + 8
-3x = 1 + 8

Combine like terms: 1 + 8 = 9
-3x = 9

Divide each side by '-3'.
x = -3

Simplifying
x = -3

See similar equations:

| Y(y-1)(y+2)=0 | | 33/20 | | 2x+0.5x+0.25x=12 | | 7.15=5.5u | | 4x/8y= | | 4.9=0.6 | | 700(1000)+1200x=1000000 | | 32=8s | | 0=(4x-1)(x-1) | | a=3.14(63)(63) | | 3x+2y=152 | | c=2(3.14)(126) | | 55x-14-35x=-133 | | 90x-1400-x^2=0 | | (X^6)^6/x^3 | | 48x-13-24x=-358 | | y=(x^2-8x+12)(x+1) | | (4/3)(3.14) | | -12(x+6)=4(x+6) | | a=3.14(13)(13) | | x+(x*2.24)=2200 | | c=2(3.14)(26) | | -13-3(t-5)= | | Logx=(x^2-12) | | X*2-6x-23=0 | | 15x+53=83 | | 37x-14+19x=-105 | | .04x+.07(11000-x)=660.00 | | a=3.14(17)(17) | | x+(x*1.88)=2200 | | a=3.14(17) | | c=43.69cm |

Equations solver categories